From Goldilocks to Gump: entrepreneurial mechanisms for everyday entrepreneurs - Sarasvathy, Saras D.; Forster, William; Ramesh, Anusha (REGEPE Entrepreneurship and Small Business Journal, 2020)
In this essay we argue that the exclusive focus on research aimed at isolating the characteristics of entrepreneurs as opposed to others, while intellectually exciting and even practically valuable, may have blinded us to another wholly new and exciting possibility – namely, the design of mechanisms that allow all kinds of individuals to start new ventures and provide useful and valuable tools to enable them and their stakeholders to build enduring organizations. The research stream on effectuation has identified a few of these mechanisms. By showing where effectuation may be located within the history of behavioral and experimental economics, we were led to the outline of at least three more mechanisms that could open the door to an entirely new research agenda on entrepreneurial mechanisms design that parallels the effort in experimental economics on economic systems design.